Comparative Assessment Of Body Indicators For Highly Qualified Athletes Specializing In Cyclic Sports - L.D. Seidalieva; G.S. Avezova (Zien Journals, 2024)
The article discusses a comparative assessment of physique indicators among highly qualified athletes specializing in cyclic sports. Studies have shown that morphological characteristics that have prognostic significance at the initial stages of a long-term training process and retain their information content as the sports skills of athletes competing in cyclic sports increase include: body length and weight, chest circumference, length of the thigh, lower leg, muscle mass of the thigh and lower leg , and the somatotype that most corresponds to the needs of this specialization is the ectomesomorphic somatotype.
Keywords: somatometric indicators; cyclic sports; ectomorphic and endomorphic components